The Management of Medical Equipment in the Challenges of the National Health System: A Review - Quiroz-Flores, C. P. (Revista Mexicana de Ingenieria Biomedica, 2020)
In this review, we describe the challenges that the National Health System must face in order to comply with the international agenda with resolutions issued by leading organizations, one of them by the World Health Organization and the other by the United Nations, it has to do with the goals for the year 2030, with the third Sustainable Development Goal: Good Health and Well-being. Mexico has structurally reformed its National Health System in order to comply as a member country. With the reform, the bases of the Universal Health Coverage were established when creating the Social Protection System in Health, the last two National Health Plans pretended to strengthen it, modify it and improve it including quality as a transversal axis to influence the attention of the health of the hospital units. To support this action, the General Health Council creates the Certification of Hospitals with standards approved by the Joint Commission, one of the indispensable standards related to the management of medical equipment, which must be carried out under guidelines dictated by national and international standards. that allow establishing policies, objectives, processes and governance structured and aligned to other international standards.